Harnessing the Power from Ambient Moisture with Hygroscopic Materials - Shen, Daozhi; Li, Fangzhou; Su, Yanjie; Zhu, Limin (Nano-Micro Letters, 2026)
Moisture electricity generation (MEG) has emerged as a sustainable and versatile energy-harvesting technology capable of converting ubiquitous environmental moisture into electrical energy, which holds great promise for renewable energy and constructing self-powered electronics. In this review, we begin by outlining the fundamental mechanisms—ion diffusion, electric double layer formation, and streaming potential—that govern charge transport for MEG in moist environments. A comprehensive survey of material innovations follows, highlighting breakthroughs in carbon-based materials, conductive polymers, hydrogels, and bio-inspired systems that enhance MEG performance, scalability, and biocompatibility. We then explore a range of device architectures, from planar and layered systems to flexible, miniaturized, and textile-integrated designs, engineered for both energy conversion and sensor integration. Key challenges are analyzed, along with strategies for overcoming them. We conclude with a forward-looking perspective on future directions, including hybrid energy systems, AI-assisted material design, and real-world deployment. This review presents a timely and comprehensive overview of MEG technologies and their trajectory toward practical and sustainable energy solutions. Highlights: 1 Typical structures/working mechanisms of moisture electricity generation (MEG) devices are comprehensively reviewed. 2 An extensive comparison of the power generation between various materials and architectures are summarized. 3 Applications, challenges, and future development directions of MEG technology, especially the artificial intelligence-assisted material discovery, are discussed.